Análisis teórico-experimental del colector solar cilíndrico parabólico automatizado con espejos reflectantes - pinedo Araujo y Cols., Anthony (2019)
in this research we show an analysis of cylindrical parabolic solar collectors (cPc), which were improved through incorporation of reflective mirrors, thus increasing their efficiency. similarly added a light monitoring system, based on photosensors, so we can maximize every sunbeam. as a first approximation it was assumed that the solar collector works as a perfect black body. Then we propose a more realistic model, where it takes into account the heat losses, dissipation of the solar rays, the optical properties of materials used, etc. in the experimental part, this system was assembled, and was compared with traditional systems of cPc. The principal result was a marked improvement in the temperature for the receiver tube in a shorter time of exposure. also, we show applications of this type of collectors, ranging from domestic heating systems, improving production anaerobic fermentation, to thermal power plants for generating electricity. in the end, we show proposals for the improvement of this system according to theoretical investigation.